1999
DOI: 10.1097/00000539-199908000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Dextromethorphan Reduces Postoperative Pain After Hysterectomy

Abstract: Patients given dextromethorphan before and after surgery had a significant reduction in some pain scores at rest, but not on movement. There was a trend to lower morphine requirements in the first 24 h. Over the next 48 h, oral analgesic usage was significantly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 15 publications
5
34
1
Order By: Relevance
“…NMDA receptor results in decreased neuronal excitability. This is the theoretical basis of the antinociceptive properties seen by dextromethorphan in previous studies (Chia et al, 1999;Henderson et al, 1999). Thus, it is theorized that blocking hypersensitization via the NMDA receptor prevents the enhanced response to painful stimuli.…”
Section: Conceptual Frameworkmentioning
confidence: 83%
See 4 more Smart Citations
“…NMDA receptor results in decreased neuronal excitability. This is the theoretical basis of the antinociceptive properties seen by dextromethorphan in previous studies (Chia et al, 1999;Henderson et al, 1999). Thus, it is theorized that blocking hypersensitization via the NMDA receptor prevents the enhanced response to painful stimuli.…”
Section: Conceptual Frameworkmentioning
confidence: 83%
“…Some studies have concluded that dextromethorphan decreases postoperative pain with a concomitant reduction in analgesic use (Chia, Liu, Chow, & Lee, 1999;Henderson, et al, 1999;Kawamata, Omote, Kawamata, & Namiki, 1998). Other studies have failed to show any effect on pain levels or amount of analgesics required (Grace et al, 1998;Rose, Cuy, Cohen, & Schreiner, 1999).…”
Section: Statement Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations